Predation by the nonnative rainbow trout, oncorhynchus mykiss (Walbaum 1792), on the native biota from freshwater environment of the central Andes (Argentina) - Rios, Juan Manuel (2021)
This study aimed to examine the impact of the nonnative rainbow trout Oncorhynchus mykiss on the native biota that inhabits freshwater environments of the central Andes, Argentina. To assess the predation pressure on native Andean vertebrates and invertebrates, the stomach contents were taken from rainbow trout caught at three Andean sites. Results showed that the major prey items were the native torrent catfish Hatcheria macraei (100% in diet), Elmidae coleopterans (23%), and the native crab Aegla affinis (38%) in the rainbow trout stomachs collected from Cipolletti Dam (North zone), Yaucha River (Middle zone), and Vaina Stream (South zone), respectively. This preliminary study exhibits the predation pressure of the rainbow trout on native Andean species and suggests that policies are necessary to control the release of fry of this exotic salmonid in the Andes region.